Subjective Well Being Pada Guru PKBM (Pusat Kegiatan Belajar Masyarakat ) Berdikari Surakarta - Mutmainah Wulan Agustina (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The purpose of this study was to determine how subjective well-being is in teachers who actively teach at PKB Berdiakri. The approach used was a qualitative method with regular interviews and observations. The results of the study revealed that PKBM Bersdikari teachers have sufficiently reflected subjective well-being in their daily lives.